In vitro germination and viability testing of Nipa (Nypa fructicans Wurmb.) pollen under different storage conditions - Mantiquilla, Junaldo A.; Elumba, Merlene; Adtoon, Jenny A.; Abad, Reynaldo G.; Millado, Cyrose Suzie Silvosa; Rivero, Gilda (2018)
Viability levels of fresh nipa (Nypa fruticans Wurmb.) pollen samples were determined using acetocarmine stain to identify viable from non-viable pollen. Regardless of the position of male spikes in the inflorescence, the general viability level was estimated at 97.80% even when pollen samples were subjected to temperature of 40 °C at 12, 24, 36, and 48 h. Pollen samples stored under different temperatures in 75 d revealed that oven-drying (40 °C) achieved 96.4% viability, which is significantly higher than deep freezer (–20 °C). Fresh pollen samples collected in Davao Region without pre-drying showed low initial viability in Bago Aplaya, while those from Hagonoy and Carmen had higher % viability due to exposure to higher temperature during longer transit. In vitro germination also showed that pollen broke open by aperture when subjected to different levels of sucrose (2, 4, 6, 8, and 10%) at different duration (1, 2, 3, 4 h). The content of the pollen was released instead of tube growth during this test, which requires further validation.
Keywords: Nypa palm